STUDY OF RISK FACTORS ON MATERNAL MORTALITY - Imelda Manurung (Journal of Health and Behavioral Science, 2022)
Maternal mortality is still a major problem in East Flores District . Therefore, this study aimed to explain the risk factors of maternal mortality. This type of research was qualitative study with a phenomenological approach. Main informant was coordinator and village midwifes. Data triangulation was carried out on the head of the health center and the MCH manager at the district health office. Data were collected through in-depth interview and analyzed with content analysis. The results showed that the factors of maternal mortality were maternal health conditions, low K4 visits, expensive transportation costs to health facilities, more priority in handling health problems in traditional and spiritual ways and delays in referrals to health facilities. For the supervision of MCH services carried out not in accordance with the guidelines. Some of the reasons found were because midwives had not received training related to the implementation of supervision, lack of budget, decree and feedback. Conclusion: The need to improve the skills of midwives in supervising MCH for efforts to improve the quality of maternal health services.